2012
DOI: 10.1007/s12639-012-0181-5
|View full text |Cite
|
Sign up to set email alerts
|

Determination of LC50 and LC95 values of fipronil against Haemaphysalis bispinosa based on adult immersion test

Abstract: The pattern of mortality of Haemaphysalis bispinosa ticks against fipronil was studied based on adult immersion test. Mortality occurred during 10-19 days post-treatment. The LC 50 and LC 95 values were calculated as 0.53 and 7.045 ppm, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…However, the application of LC 50 every 30 days also has a beneficial effect since it manages to reduce the population size in a short time (in four months it decimates the initial population of adults by 50%) and does not require extra expenditure of material for its potential implementation as LC 95 . [19][20] Therefore, it is concluded that the extract of H. riparia leaves was the most efficient for controlling A. aegypti populations, so they deserve to be studied in depth given their potential larvicidal effect. Similar results were obtained by Alvarez-Valverde et al (2023) [29] when they applied powdered leaves of Ipomoea cairica on having the lowest LC 50 of 0.0341 mg/mL offered to A. aegypti, arguing that the differences were due to the protection that the wheat grain provided to the insect.…”
Section: Discussionmentioning
confidence: 99%
“…However, the application of LC 50 every 30 days also has a beneficial effect since it manages to reduce the population size in a short time (in four months it decimates the initial population of adults by 50%) and does not require extra expenditure of material for its potential implementation as LC 95 . [19][20] Therefore, it is concluded that the extract of H. riparia leaves was the most efficient for controlling A. aegypti populations, so they deserve to be studied in depth given their potential larvicidal effect. Similar results were obtained by Alvarez-Valverde et al (2023) [29] when they applied powdered leaves of Ipomoea cairica on having the lowest LC 50 of 0.0341 mg/mL offered to A. aegypti, arguing that the differences were due to the protection that the wheat grain provided to the insect.…”
Section: Discussionmentioning
confidence: 99%